The grapes of wrath [videorecording (DVD)] - Ford, John, 1894-1973; Fonda, Henry, 1905-1982; Darwell, Jane, 1880-1967; Carradine, John; Grapewin, Charles, 1869-1956; Steinbeck, John, 1902-1968 (20th Century Fox Home Entertainment, 2007)
The migration of the Joad family to California from their dust-bowl farm in Oklahoma during the Great Depression.